2006
DOI: 10.1196/annals.1346.011
|View full text |Cite
|
Sign up to set email alerts
|

The Pericellular Matrix as a Transducer of Biomechanical and Biochemical Signals in Articular Cartilage

Abstract: The pericellular matrix (PCM) is a narrow tissue region surrounding chondrocytes in articular cartilage, which together with the enclosed cell(s) has been termed the "chondron." While the function of this region is not fully understood, it is hypothesized to have important biological and biomechanical functions. In this article, we review a number of studies that have investigated the structure, composition, mechanical properties, and biomechanical role of the chondrocyte PCM. This region has been shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
250
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(256 citation statements)
references
References 74 publications
3
250
1
2
Order By: Relevance
“…Moreover, whereas compressive loading of intact cartilage explants can stimulate proteoglycan synthesis immediately (1,27), the response of chondrocytes embedded in agarose is enhanced with additional weeks of preculture (28). Cell-matrix interactions in the pericellular region are believed to play a critical role in transducing mechanical signals (29)(30)(31). Several studies smaller than all other groups (P < 0.05); **less than control and GSK205, greater than Loaded+GSK205 (P < 0.05), n = 4-6, mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, whereas compressive loading of intact cartilage explants can stimulate proteoglycan synthesis immediately (1,27), the response of chondrocytes embedded in agarose is enhanced with additional weeks of preculture (28). Cell-matrix interactions in the pericellular region are believed to play a critical role in transducing mechanical signals (29)(30)(31). Several studies smaller than all other groups (P < 0.05); **less than control and GSK205, greater than Loaded+GSK205 (P < 0.05), n = 4-6, mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed [Ca 2+ ] i signaling in response to mechanical loading (38,39); interestingly, these studies detected [Ca 2+ ] i signaling in chondrocyte-laden constructs without substantial preculture (<72 h), although chondrocytes synthesize small amounts of pericellular proteoglycans even within 2 d of culture in agarose (29) that could contribute to mechanically induced [Ca 2+ ] i signaling. Thus, the effects of loading with and without preculture, observed in this study as well as in previous studies, may be due to differences in the characteristics of the [Ca 2+ ] i signal with preculture, or perhaps other environmental and cellular factors that change over time (24,26,28,40).…”
Section: Camentioning
confidence: 99%
“…In mature articular cartilage, WARP has a highly restricted localization in the chondrocyte pericellular matrix, a structure with important roles in facilitating cellmatrix interactions and in maintaining cartilage homeostasis, particularly in detecting and responding to changes in mechanical stimuli (26,27). We predicted that ablating WARP expression would disrupt the pericellular matrix, which may alter interactions of chondrocytes with their surrounding matrix and, potentially, their response to mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…The strings of mid and inner annular cells embedded in a dense pericellular matrix, located between adjacent lamellae, largely spared these tensile strains. However, the annular cells of the outer AF with their extensive interdigitating cellular processes woven into the collagenous architecture would be expected to be subjected to tensional forces in situ and may be involved in annular mechanotransduction events [38]. The morphologic complexity of the annular cells with their interwoven ECM attachments to the annular collagen fibres indicates that the load transfer from ECM to cell membrane to cytoskeleton in all likelihood occurs by a complex pathway.…”
Section: The Pericellular Matrix Cell-matrix Interactions and Annulamentioning
confidence: 99%